Speciation of nickel and zinc, its short-term inhibitory effect on anammox, and the associated microbial community composition - KALKAN AKTAN, ÇİĞDEM; BAKIRCI, KOZET (ELSEVIER SCI LTD, 2018)
This study provides insight into the short-term effects of nickel and zinc on anammox. The impacts of these heavy metals are evaluated based on their potentially bioavailable fractions, including the intracellular, surface-bound, soluble, free-ion, and weak (labile) complexes of heavy metals, in the presence of certain inorganic/ organic species. Results showed that the IC50 values for soluble, intracellular, cell-associated, surface-bound, and free-ion Ni concentrations are 5.99, 0.250, 0.930, 0.680, and 1.36 mg/L, respectively. The inhibitory effect of Zn is found to be lower with respect to Ni, with 1050 values of 6.76, 11.9, 15.1, and 2.71 mg/L for the soluble, intracellular, cell-associated, and free-ion Zn concentrations, respectively. This is the first detailed evaluation of anammox inhibition based on the fractionation of heavy metals. Metagenomic analysis reveals that Candidates Kuenenia constitute approximately 89% of the entire Planctomycetes population, whereas Candidates Brocadia are detected in relatively low fractions (3%).
Keywords: Anammox; Nickel; Zinc; Inhibition; Next generation sequencing; AMMONIUM OXIDATION ANAMMOX; HEAVY-METALS; ACTIVATED-SLUDGE; LANDFILL LEACHATE; NITROGEN REMOVAL; ORGANIC-MATTER; NITRIFICATION; PERFORMANCE; DENITRIFICATION; RECOVERY